2022
DOI: 10.2196/36068
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Peer Support Mobile App and Web-Based Lesson for Adolescent Mental Health (Mind Your Mate): User-Centered Design Approach

Abstract: Background Digital technologies and mobile interventions are possible tools for prevention initiatives to target the substantial social and economic impacts that anxiety, mood, and substance use disorders have on young people. Objective This paper described the design and development of the Mind your Mate program, a smartphone app and introductory classroom lesson enhancing peer support around the topics of anxiety, depression, and substance use for ado… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It was designed in collaboration with young people and experts in mental health and substance use prevention. Key content and module selection was based on a scoping review of the literature, a survey and focus groups with young people, and evidence-based mental health and substance use prevention strategies (full details of the development process have been previously published [ 19 ]). The intervention included 1 introductory web-based classroom lesson, led by a teacher, and a self-directed mobile app.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was designed in collaboration with young people and experts in mental health and substance use prevention. Key content and module selection was based on a scoping review of the literature, a survey and focus groups with young people, and evidence-based mental health and substance use prevention strategies (full details of the development process have been previously published [ 19 ]). The intervention included 1 introductory web-based classroom lesson, led by a teacher, and a self-directed mobile app.…”
Section: Methodsmentioning
confidence: 99%
“…The app is a self-guided program that builds upon the concepts introduced in the classroom lesson by providing normative information about mental health and substance use, skill-building modules for peer support (including active listening and checking in), self-care modules, as well as referral and support options to encourage further help seeking. Full details regarding the app development process, app features, and functionality have been previously published [ 18 , 19 ]. The next step was to evaluate the effectiveness of the program in improving youth mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Most research available on peer support apps focuses on serious mental and physical health challenges, such as bipolar disorder, schizophrenia, or major depressive disorder [39][40][41][42][43], those with cancer [38], and those who self-harm [44,45]. In some cases, a mental health app is used along with peer support rather than a peer support app per se [39,40] or involves the process of creating a peer support app [46].…”
Section: Mental Health Appsmentioning
confidence: 99%
“…Evidence has demonstrated that user-centered design increases the likelihood that interventions will be used by the end user [64,71,72] and has been used in the development of other digital interventions. A user-centered design has been used in the development of other digital interventions for substance use prevention among adults [73,74] and adolescents [75].…”
Section: Framework That Informed Approach To Game Developmentmentioning
confidence: 99%
“…On the basis of the information gleaned from our development focus groups and interviews, our research team collaborated with our game development partners, Schell Games, to launch and finalize the video game intervention, PlaySmart. Game content was directly informed by focus groups and interviews, similar to other digital interventions targeting adolescents [29,30,53,54,75,[81][82][83][84].…”
Section: Development: Playsmart Video Game Interventionmentioning
confidence: 99%